Renewable energy and climate change - Quaschning, Volker, 1969- (Chichester, West Sussex, U.K. ; Hoboken, N.J. : Wiley, 2010)
Renewable Energy is a clear introduction to the topics of climate protection and renewable energy, demonstrating the correlations between use of energy, energy prices, and climate change. It evaluates and analyzes the current world situation, whilst also giving essential and practical guidance on personal climate protection.
TOC
Includes bibliographical references (p. 300-302) and index.
Sociology
Sagar Shahanawaz
Keywords: Renewable energy sources; Climatic changes